Study & Comparison of Drug Approval Process for Different Countries in Relation to Authorisation Agency & Clinical Trials - Mukati, Shivangi (International Journal of Pharmaceutical & Biological Archive, 2018)
In this review paper we are discussing drug approval process for different countries i.e. USA, EU, Australia and India. It is a known factor that different countries are having different drug approval processes worldwide. The basic aim of present work is to study the Comparison of Drug Approval Process for Different Countries in Authorisation Agency & Clinical Trials.